2021
DOI: 10.3390/toxics9080174
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Relevant Mixture of Pesticides Affect Mobility and DNA Integrity of Early Life Stages of Rainbow Trout (Oncorhynchus mykiss)

Abstract: The aim of this study was to analyze the impact of three concentrations of a pesticide mixture on the first development stages of rainbow trout (Oncorhynchus mykiss). The mixture was made up of three commonly used pesticides in viticulture: glyphosate (GLY), chlorpyrifos (CPF) and copper sulfate (Cu). Eyed stage embryos were exposed for 3 weeks to three concentrations of the pesticide mixture. Lethal and sub-lethal effects were assessed through a number of phenotypic and molecular endpoints including survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Another approach to assess effects of mixtures of neuroactive chemicals, is to use their recorded concentrations in the environment. Santos et al 2021 [ 11 ] analyzed the impact of mixtures of relevant concentrations of three common pesticides, glyphosate, chlorpyrifos and copper, over developmental stages of rainbow trout ( Oncorhyncus mykiss ). The authors found antagonistic effects over fish swimming activity when exposed to chemicals with opposing effects.…”
mentioning
confidence: 99%
“…Another approach to assess effects of mixtures of neuroactive chemicals, is to use their recorded concentrations in the environment. Santos et al 2021 [ 11 ] analyzed the impact of mixtures of relevant concentrations of three common pesticides, glyphosate, chlorpyrifos and copper, over developmental stages of rainbow trout ( Oncorhyncus mykiss ). The authors found antagonistic effects over fish swimming activity when exposed to chemicals with opposing effects.…”
mentioning
confidence: 99%